2021
DOI: 10.1016/j.phro.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance guided elective neck irradiation targeting individual lymph nodes: A new concept

Abstract: Highlights Individual elective lymph nodes can be identified using multiple Dixon T2-weighted turbo spin echo with fat suppression. Magnetic Resonance guided individual lymph node irradiation results in lower dose to the organs at risk. Especially the submandibular glands, carotid arteries and thyroid can be spared. The magnetic field on the magnetic resonance imaging - linear accelerator did not lead to increased skin dose depositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The next step in elective lymph node irradiation is a new concept of individual lymph node irradiation, which was introduced in 2021 [ 103 ]. The idea of this concept is to target all individual lymph nodes visible on T2-weighted MR images ( Figure 4 ).…”
Section: Future Perspectives On Target Definition For Hnscc Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The next step in elective lymph node irradiation is a new concept of individual lymph node irradiation, which was introduced in 2021 [ 103 ]. The idea of this concept is to target all individual lymph nodes visible on T2-weighted MR images ( Figure 4 ).…”
Section: Future Perspectives On Target Definition For Hnscc Treatmentsmentioning
confidence: 99%
“…The idea of this concept is to target all individual lymph nodes visible on T2-weighted MR images ( Figure 4 ). A planning study in laryngeal cancer patients showed that such a strategy results in a reduction in mean dose values to OARs up to 20 Gy [ 103 ]. A prerequisite for the implementation of this concept is having access to an MR-guided treatment modality, as small individual lymph nodes are not visible on cone beam CT, and day-to-day variation due to motion and shifts in individual lymph nodes needs to be corrected for.…”
Section: Future Perspectives On Target Definition For Hnscc Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we proved that large dose reductions (>5 Gy) could be achieved with elective lymph node irradiation for several Organs At Risk (OARs) such as the submandibular glands, carotid arteries and thyroid [14] . In another study, the MRI visibility and displacement of elective lymph nodes during radiotherapy in HNC patients was described [15] , in order to estimate safe inter-fraction radiotherapy margins for this new treatment concept.…”
Section: Introductionmentioning
confidence: 99%
“…All studies use conventional lymph node levels for ENI based on Computed-Tomography (CT) according to international guidelines [13] . However, with modern imaging modalities such as Magnetic Resonance Imaging (MRI) smaller soft tissue structures, such as individual lymph nodes, can be better visualized compared to CT [14] . As occult metastases are expected to harbor inside lymph nodes, it would be logical to restrict ENI to only individual lymph nodes instead of the larger lymph node levels they are located in.…”
Section: Introductionmentioning
confidence: 99%